Ben Sira’s Teaching on Friendship - Corley, Jeremy (Book collections on Project MUSE., 2020)
"The purpose of this study is to elucidate Ben Sira's teaching on friendship within the religious and cultural context of his time, in view of the Hellenistic emphasis on philia ("friendship"). While friendship is of contemporary interest, until recently there has been little research into the understanding of friendship in Second Temple Judaism. This study aims to fill the lacuna by focusing on the apocryphal/deuterocanonical Wisdom of Ben Sira (Sirach). In fact, no book of the Hebrew Bible says as much about friendship as does the Wisdom of Ben Sira."--Provided by publisher